THE INFLUENCE OF PRODUCTS, PRICES, PROMOTIONS, AND PLACES ON PURCHASE DECISIONS AT PANGLONG SAKAI SAMBAYAN IN BRANTI RAYA SOUTH LAMPUNG - Muhammad Amar Qusay; Ni Putu Widhia Rahayu (ZILLZELL MEDIA PRIMA, 2026)
This study is focused on examining the contribution level of purchase decisions determined by product, price, promotion, and location factors. This study makes all consumers who make purchase transactions during 2025 as a research population, with a total population of 110 study subjects. The quantity of study respondents adapting the calculation to Slovin calculation with a 5% degree of error was recorded as 86 individuals as study respondents. Referring to the results of the interpretation of quantitative empirical evidence through a review of multiple linear regression mechanisms, the regression mathematical equation Y = 0.454X1 + 0.54X2 + 0.046X3 + 0.245X4 + e was identified. Testing per aspect by t-test indicates that the product, price, and promotion determine the purchase decision, while the place aspect does not determine individually. However, the results of the F test prove that all triggering factors collectively influence the purchase decision at Panglong Sakai Sambayan. The value of the determination coefficient proves that promotion, location, and price show a determination contribution of 52.6% to the purchase action.